APLIKASI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK PERENCANAAN PENGEMBANGAN TAMBAK BIOCRETE - Susilo Budi Priyono; Sri Rahayu (Jurnal Perikanan Universitas Gadjah Mada, 2003)
Application of remote sensing and geographic information system (GIS) for planning of biocrete shrimp ponds development was studied in the coastal area between Opak River and Progo River, Bantul Regency. Analysis of land suitability for biocreteshrimp pond used a multi-scoring of some physical variables, i.e. slope, soil texture, distance from coast line, distance from river, annual rainfall, flooded frequency, and landuse. Spatial analysis used a GIS software (ER Mapper 5.5, ARC/Info 3.5 and ARC/View GIS 3.2). The results showed that suitable land fotbiocreteshrimp pond was 73,6 ha. It found on beach ridge area that was distributed at Srandakan, Sanden, and Kretek Region. However, considered on the Detail Planning of Spatial Arrangement at Southern Coastal of Bantul Regency (RDTK PantaiSelaatnKabupatenBantul) and suistanable aquaculture planning, the development of biocrete shrimp ponds should be limited to 36,8 ha (50%), i.e. 18,4 ha ponds at Srandakan and 18,4 ha ponds at Sanden. Biocrete shrimp ponds had to be built at distance about 300 m from cost line.